Antifungal Activity of Local Anesthetics Against Candida Species - Cidália Pina-Vaz; Acácio Gonçalves Rodrigues; Filipe Sansonetty; J. Martinez-; António F. Fonseca; Per-Anders Mårdh (Hindawi Limited, 2000)
Objective: To evaluate the activity of benzydamine, lidocaine, and bupivacaine, three drugs with local anesthetic activity, against Candida albicans and non-albicans strains and to clarify their mechanism of activity.